Plasma Kinetics in Deuterium-Filled Plasma Focus with Step Anode Configuration - Mohamad, S. N; Rashid, N. Abd; Chaudhary, K.; Lee, S.*; Saw, S. H.; Jalil, Ali (American Scientific Publishers, 2015)
A numerical analysis of a plasma focus device with step anode as the central electrode is carried out with Lee Model Code for a stepped central electrode configuration. The snowplow model is employed to describe the dynamics of current sheath between the electrodes using momentum conservation of the swept gases. The discharge current and the tube voltage are determined by circuit equation. Different plasma parameters including plasma temperature and speed of current sheath are simulated for the step anode configuration. The step anode model is compared with the standard electrode configuration to observe the dynamical behaviour of the plasma during the axial and radial phase. The results indicate that the current dip and the spike voltage are slightly higher and an increase in the speed of current sheath at both axial and radial phases are observed. The step anode has shown peak current of 0.4% less than the cylindrical anode. However, the current sheath speed is enhanced at both axial and radial phases up to 20.1% for step anode configuration. The step anode configuration is also contributed to rise the plasma pinch temperature. The new configured anode in Lee's model can carry a new tube parameter for optimizing the plasma focus device for SXR yield and neutron yield based on numerical experiment.